Generation of two isogenic control lines by correcting the BAG3 P209L mutation of human induced pluripotent stem cell (hiPSC) lines from patients with myofibrillar myopathy-6 - Kerstin Filippi; Martin Wiemann; Bernd K. Fleischmann; Michael Hesse (Stem Cell Research)
BAG3 plays a key role in proteostasis as a central component of the chaperone-assisted selective autophagy (CASA) complex. A point mutation (p.P209L; c.626C>T) in the BAG3 gene causes severe myofibrillar myopathy-6 (MFM6), restrictive cardiomyopathy and polyneuropathy leading to muscle weakness and heart failure. Establishing suitable controls for patient-derived BAG3P209L/WT-induced pluripotent stem cells (iPSCs), two isogenic controls were generated by correcting the point mutation c.626C>T in iPSCs from two MFM6-patients. We performed quality control of these lines by differentiation into the three germ layers and pluripotency tests. These isogenic hiPSC-control lines allow the correct analysis of MFM6 using corresponding patient-specific iPSCs.